Topological Interface States of Shear Horizontal Guided Wave in One‐Dimensional Phononic Quasicrystal Slabs. Issue 10 (21st August 2018) - Zhao, Jiaming; Huo, Shaoyong; Huang, Hongbo; Chen, Jiujiu
Abstract : In this Letter, the topological interface states of shear horizontal guided wave are investigated in a one‐dimension (1D) phononic quasicrystal system. It has been found that multiple interface modes can occur at the interface of two Fibonacci sequences slabs. The occurrence of the interface states is determined by the condition that the sum of the left and right surface impedances of the interface is equal to zero. Most significantly, as the generation number of the Fibonacci sequence increases, more interface states will come into being at the interface of the quasi‐periodic slabs, which is caused by the accumulation of the detuning. This study of the topological interface states in phononic quasicrystals will greatly enrich the knowledge on the topology and broaden its application scopes. Abstract : Phononic quasicrystal generated by the Penrose method (octagonal quasicrystal) or the substitution algorithm (Fibonacci slab) holds rich topological properties. The multiple topological interface states with large sound intensity enhancement and high transmission in Fibonacci slabs have been studied, which have promising value in both scientific research and engineering applications, such as sound detection and biomedical imaging.